JUDGING THE JUDGES - Chan, Nyarn Hoi, 1935-, author 568753 (Petaling Jaya : Alpha Sigma, 2007)
The book is about the role of the judge in the community for which he serves. The narrative is a compelling account of the judge's craft which is written in a most readablestyle. Judge Chan writes on difficult questions of law which can easily be understood by ordinary folk. This is as much in his writing style as can be seen in his judgments which he quotes extensively from to illustrate his point of view in the book. As the title of the book suggests, only when one is able to understand what the craft of the judge is about that one may be able to judge the performance of the judges. And it is only then will ordinary folk be able to tell the difference between the good and the bad judges. The aim of the book is to let ordinary folk know when a judge has done something wrong and so could be faulted. As for the judges, they should know their craft and this book hopes to remind them of that lest they forget.